2013
DOI: 10.7567/jjap.52.09ld15
|View full text |Cite
|
Sign up to set email alerts
|

Page Data Multiplexing for Vector Wave Memories Having Polarization Recording Material Doped with Aromatic Ketone Derivative

Abstract: We have developed a new polarization recording material doped with the photodegradative aromatic ketone derivative AK1-H, modified from our conventional material AK1 for vector wave memories (VWMs) to improve signal stability as well as recording characteristics. 10-multiplex page data recording was performed for the first time in VWMs with AK1-H, exhibiting a signal-to-noise ratio of 3 or higher and an estimated symbol error rate of 10-4 or lower for most pages, respectively. VWM media having AK1-H were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…This new type of polarization-sensitive material with AK1 has higher photoinduced birefringence than that with PQ polarization-sensitive materials as photoinitiators are expected to improve the properties of polarized holographic recording materials. In 2013, they developed an improved polarization-sensitive photopolymer material with AK1-H [51]. With optimized photosensitizer AK1-H doped, the conventional material AK1 for vector wave memories (VWMs) was modified to improve signal stability and recording characteristics.…”
Section: Photopolymer Materialsmentioning
confidence: 99%
“…This new type of polarization-sensitive material with AK1 has higher photoinduced birefringence than that with PQ polarization-sensitive materials as photoinitiators are expected to improve the properties of polarized holographic recording materials. In 2013, they developed an improved polarization-sensitive photopolymer material with AK1-H [51]. With optimized photosensitizer AK1-H doped, the conventional material AK1 for vector wave memories (VWMs) was modified to improve signal stability and recording characteristics.…”
Section: Photopolymer Materialsmentioning
confidence: 99%
“…In 2013, Ando et al synthesized a polymer PSO 3 and co-doped PMMA with PQ and the polymer PSO 3 [ 124 ]. The experiment showed that a small amount of PSO 3 can greatly improve holographic performance, with the maximum diffraction efficiency reaching 54%.…”
Section: Origins Of Pq/pmma and Performance Improvement Measuresmentioning
confidence: 99%